STRATEGI GURU PENDIDIKAN AGAMA ISLAM dalam MENUMBUHKAN PERILAKU BERAGAMA SISWA di MADRASAH IBTIDAIYAH (MI) SYECH QURRA AL ALAWY KOTA BARU KARAWANG - Faridah; Ibnu Muthi; Asep Dudin Abdul Latip (FAKULTAS TARBIYAH IAI SULTAN MUHAMMAD SYAFIUDDIN SAMBAS, 2021)
MI Sheikh Qurra. included in the superior school category, this study discusses how students' religious behavior and teacher strategies in schools and the focus of the research leads to three things, namely about students' religious behavior, Islamic Religious Education teacher strategies to foster religious behavior, as well as supporting and inhibiting factors in efforts to foster religious behavior. student of MI Syach Qurra Allawy. The creation of a religious atmosphere is strongly influenced by the situation and conditions of the place and the application of the underlying values. The creation of a vertical religious culture can be realized in the form of increasing the relationship with God, the quality of religious activities in schools that are ubudiyah in nature, and the creation of a horizontal religious culture that is more placing schools as religious social institutions, which when viewed from the structure of human relations are equal. or voluntary based on religious values ​​such as: brotherhood, generosity, honesty, mutual respect and so on. The research focused on 1 Madrasah Ibtidaiyah namely MI Syeh Qurra Alalawy located in the Kab. Karawang. The research uses qualitative research, case study methods, a research procedure that produces descriptive data in the form of written or oral data from people and behaviors that can be observed as research objects, deepening by making observations, reviewing documents and interviews. It was concluded that the religious behavior of MI Syech Qurra students was quite visible in their daily activities and activities such as reading greetings to meet teachers, praying before and after studying, praying in congregation, praying Duha, reading the Qur'an, participating in religious extracurricular activities, participating in activities Islamic holidays, the implementation of the five daily prayers of students, social solidarity of students, student behavior towards teachers and other students and efforts to fill students' free time. The strategy of Islamic Religious Education (PAI) teachers in cultivating the religious behavior of MI Syech Qurra Alalawy students in several ways, namely: by giving advice and motivation, invitations to pray, religious habits, Religious Eskul. Reward and funism, Take a functional approach and emotional. Discipline in schools. Student Journal Book, Islamic Holidays are held. Religious competitions and intense communication with parents. The supporting factors for the school's internal support are from the academic community and the school's external support is the support from students' parents. School Committee. Local communities. Alumni and Supporting Facilities. The inhibiting factors are the minimal budget, the limited number of teachers and education staff, weak mastery of technology, limited facilities, weather and climate conditions and there are parents who are weak in response. Principals are expected to continue to maintain their role in building and realizing schools where students behave in a religious manner even more.